Water monitoring system design for data collection at specific intervals via cloud application. Issue 1 (February 2021) - Abdul Muta'Ali, A N; Sazali, N; Ghani, S A C; Walter, J
Abstract: With the growing issue of water pollution and resources, the need for a remote water monitoring system has never been more crucial. The implementation of remote monitoring systems has a growing interest in the current technology development. This project aims to design a water monitoring system via cloud application. Based on previous research and papers written on the topic, a few system designs have been theorized but not implemented. In this project, the data is transmitted through the combination of LoRa and Wi-Fi connection. The system is also powered by rechargeable battery and solar panels. The communication using long range achieved a distance test of 898 m. The full system has the capability to be deployed in a distance and have the data collected uploaded to a cloud. A web server accessed through the local IP address serves the user interface that provides current data of the water parameters.